2007
DOI: 10.1007/s10681-007-9640-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity and relationships of fruit quality traits in apricot (Prunus armeniaca L.) germplasm

Abstract: Fruit quality attributes were studied for two consecutive years in forty-three apricot cultivars and selections grown in a Mediterranean climate. Physical parameters (weight, size, flesh and skin colour, percentage of blush, firmness and percentage of dry matter), chemical parameters (total soluble solids content and acidity) and sensory parameters (attractiveness, taste, aroma and texture) were evaluated. A high variability was found in the set of the evaluated apricot genotypes and significant differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
105
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(146 citation statements)
references
References 41 publications
37
105
4
Order By: Relevance
“…In addition, Ishag et al (2009) reported that TS contents of the fresh apricot cultivars was 11.8%. Our range of values is in agreement with previous works on apricot (Audergon et al 1990;Ruiz & Egea 2008b), but the values are generally lower than those for a group of Turkish genotypes (Balta et al 2002;Asma & Ozturk 2005;Asma et al 2007). The differences between the present results and those of the above mentioned authors were likely due to the different eco-geographical groups of apricot genotypes studied and the environmental conditions.…”
Section: Evaluation Of Chemical Attributessupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, Ishag et al (2009) reported that TS contents of the fresh apricot cultivars was 11.8%. Our range of values is in agreement with previous works on apricot (Audergon et al 1990;Ruiz & Egea 2008b), but the values are generally lower than those for a group of Turkish genotypes (Balta et al 2002;Asma & Ozturk 2005;Asma et al 2007). The differences between the present results and those of the above mentioned authors were likely due to the different eco-geographical groups of apricot genotypes studied and the environmental conditions.…”
Section: Evaluation Of Chemical Attributessupporting
confidence: 93%
“…SS was significantly correlated with RS or TS (r = 0.658 and r = 0.662, respectively) (Gurrieri et al 2001;Ledbetter et al 2006), while no relationship between SS and TA was found, as reported previously by Ruiz and Egea (2008b) (Table 3). A negative significant correlation was observed for TA versus SS/TA ratio (r = -0.897), and TA versus pH (r = -0.659) indicating the tendency of higher TA content to have smaller SS/TA ratio and lower pH.…”
Section: Correlations Between Variablessupporting
confidence: 67%
See 3 more Smart Citations